2021
DOI: 10.15420/aer.2020.28
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic High-density Functional Substrate Mapping Improves Outcomes in Ischaemic Ventricular Tachycardia Ablation: Sense Protocol Functional Substrate Mapping and Other Functional Mapping Techniques

Abstract: Post-infarct-related ventricular tachycardia (VT) occurs due to reentry over surviving fibres within ventricular scar tissue. The mapping and ablation of patients in VT remains a challenge when VT is poorly tolerated and in cases in which VT is non-sustained or not inducible. Conventional substrate mapping techniques are limited by the ambiguity of substrate characterisation methods and the variety of mapping tools, which may record signals differently based on their bipolar spacing and electrode size. Real wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Therefore, LVAs acquired using GMC could remain unaffected by differences in potential propagation. 10,11 Regarding the third finding, we noted that mapping using a catheter with more electrodes resulted in more points and less LVA according to various previous studies. 8 This is because number of points acquired per heartbeat increases with number of electrodes, and it seems reasonable that total number of points acquired increases using catheters with more electrodes.…”
Section: Characteristicsmentioning
confidence: 54%
See 1 more Smart Citation
“…Therefore, LVAs acquired using GMC could remain unaffected by differences in potential propagation. 10,11 Regarding the third finding, we noted that mapping using a catheter with more electrodes resulted in more points and less LVA according to various previous studies. 8 This is because number of points acquired per heartbeat increases with number of electrodes, and it seems reasonable that total number of points acquired increases using catheters with more electrodes.…”
Section: Characteristicsmentioning
confidence: 54%
“…The GMC selects the highest amplitude bipolar signal among accepted signals within a vicinity of >1 mm 2 . Therefore, LVAs acquired using GMC could remain unaffected by differences in potential propagation 10,11 …”
Section: Discussionmentioning
confidence: 99%
“…This technique may add to the armamentum of the clinical electrophysiologist to complement current methods of substrate mapping. 23 An example is in the detection of slow uniform propagation associated with late activation during sinus rhythm, which is aligned with the VT isthmus long-axis and can be utilized for its localization. The last sinus rhythm activation point is typically in proximity to the VT isthmus entrance.…”
Section: Clinical Correlatesmentioning
confidence: 99%
“…It is known that isochronal late activation mapping (ILAM) in the sinus rhythm is used in RFA treatment of atrial and ventricular tachycardias documented but not induced during the electrophysiological study (EPS) [ 3 6 ]. In late potential mapping, it was observed that fragmented recordings were prolonged by constant pacing, and it was suggested that these areas may actively participate in tachycardia [ 7 ].…”
Section: Introductionmentioning
confidence: 99%